The effect of different dosage and duration of lansoprazole-clarithromycin- amoxycillin combination on Helicobacter pylori eradication - İrfan SOYKAN,; Hülya ÇETİNKAYA,; Cansel TÜRKAY,; Ali ÖZDEN, (Turkish Journal of Gastroenterology, 2019)
-